Profile of Character-Based Online Response Assessment in the Practical Class of Fundamental Physics Muhammadiyah University of Makassar - Nurlina; Hikmah Marisda, Dewi; Dhiqfaini Sultan, Ana; Bundu, Patta (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to describe the online response assessment in the Fundamental Physics I Practical Class at Muhammadiyah University of Makassar and to find out the validity and reliability of the character-based online response assessment in the practical course of Fundamental Physics I. This research is categorized as research and development with a four-D model, which includes four stages, namely defining, designing, developing, and disseminating. This research was conducted at the Faculty of Teacher Training and Education (FKIP) at Muhammadiyah University of Makassar. The research subjects were students of the Physics Education study program who took the Basic Physics Practicum course: 1 of the 30 people and the laboratory assistant of 8 people. The result of this research was a set of assessments in the form of online-based response assessment instruments that has been through (1) expert validation, (2) revisions based on validator’s assessment, suggestions, and comments, (3) tryout, and (4) revisions based on data analysis of trial results and suggestions from laboratory assistants. Furthermore, the assessment instrument is declared eligible to be used in limited socialization, and based on analytical results, the instrument of a character-based online response assessment on the course of Fundamental Physics I is valid, reliable, and practical.